(untitled) (American Journal of Islam and Society, 2016)
This book is meant for non-Muslims who want to understand the Qur’an but are perplexed by it. Describing it as a complex book, neither thematic nor chronological, but elliptical with much of its content out of reach of the uninitiated, Michael Birkel explores how it is interpreted among North American Muslims. From the beginning, this non-Muslim author highlights the diversity of approaches and manages to present accessible “insider’s” views. Its seven sections contain a selection of voices obtained through personal interaction with the twenty-four Muslim contributors, a brief introduction, and a closing conclusion. The first contribution, “The Mother of the Book,” reflects upon how the Qur’an’s first chapter is both foundational as its “opening” and opens hearts throughout each of the five daily prayers. The two partner pieces, “Knowledge Hidden and Manifest,” focus on the Qur’anic accounts of Joseph (by Ingrid Mattson) and the encounter between Moses and the mysterious Khidr (by Maria Dakake). The themes of both stories, namely, faith and wisdom, draw the reader into the wider theme of aligning oneself with God. The author then moves on to his second theme: “Close Readings, Old and New.” Mohammad Hassan Khalil discusses God’s mercy with the phrase “In the name of God, the Compassionate, the Merciful,” which appears at the beginning of all but one sūrah. He wrestles with the idea of an everlasting hell, having discovered as a student that some Muslim scholars challenge it on the basis of God’s mercy. Alongside this “shocking” (his expression) opinion, he also came across the conviction that non-Muslims would receive God’s mercy in the Hereafter. Challenging negative readings of the Qur’an, he says, “Reading the Qur’an under the benevolent shadow of raḥma allows one to appreciate Scripture on a different level” (p. 37) ...